Physiological Behaviour of Camel with Different Draught and Work-Rest Cycles in Field Operations - Tiwari, G S; Pradeep, Dharm; Garg, Rajeev (Journal of Agricultural Engineering, 2005)
Camels of different age and body weights were selected randomly from a village in Bikaner District. The draught equivalent to 16, 18 and 20 % of body weight of camels were applied by using a multipurpose tool frame with tillage tools. Draught was varied by increasing/ decreasing the number of tynes and depth of operation. Physiological responses like pulse rate, respiration rate, body temperature and speed were recorded at all draught levels with three work rest cycles, namely WR1: 4h (W)- 5h (R)- 4h (W), WR2 : 3h (W)- 1h (R)- 2h (W)- 4h (R)-3h (W) and WR3 : 2h (W)- 1h (R) 2h (W)- 4h (R)- 2h (W)- 1h (R)- 2h (W). Maximum increase in physiological responses was observed with work rest cycle WR1. The increase in pulse rate, respiration rate and body temperature were 35 to 62 beats/min, 10 to 18 breaths/min and 37.5 to 39.2degree C respectively with WR1 while these were found minimum with WR3 in the range of 33 to 51 beats/min, 8 to 12 breaths/min and 37.3 to 38.4degree C respectively. On the basis of physiological responses work rest cycles WR3 was found better as compared to other work rest cycles.